TECHNOLOGY FORMING THE GNOSTIC COMPETENCE OF FUTURE TEACHERS OF FOREIGN LANGUAGE - Khamdamov Erkin Ergashevich , Dushaeva Sohiba Yanikulovna , Kusieva Nodira Khabibzhonovna , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article discusses a number of technologies that contribute to the development of professional competence of students, among which: independent educational activity, which determines the ability of a future language teacher's language personality to practically reorganize their own activities, which leads to an interlingual and intercultural language personality. The article considers a number of technologies that contribute to the development of students' professional competence, among which are: independent educational activity, which determines the ability of the linguistic personality of a future foreign language teacher to practically reorganize their own activities, which leads to an inter lingual and intercultural language personality.